Farm-retail price transmission in Malaysian pork sector - Yeong-Sheng, Tey (John); Stringer , Randy; Umberger, Wendy (Applied Studies in Agribusiness and Commerce, 2010)
This study intends to determine the farm-retail price transmission behaviors of pork in Malaysia to serve as a good implication for pork pricing system in Malaysia. Using monthly data from January 1997 to December 2008, markup pricing model, Houck, and ECM approaches were estimated. While many previous studies found that farm-retail price transmission is asymmetric, this study encountered different result where the findings in both the Houck and ECM approaches suggested that the Malaysian pork farm-retail price transmission is symmetric. A change in farm price of pork is likely to have similar direction in change of retail price of pork in Malaysia. The pricing system of pork can therefore be further described by the estimated price transmission elasticities (that derived from the symmetric mark-up pricing model) where retail price is very sensitive to the changes in farm price. A change in farm price is expected to result in a bigger change in retail price of pork while other things remain unchanged.